1998
DOI: 10.1111/j.1530-0277.1998.tb03646.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Alcohol Affects the Ability to Maintain Postural Balance

Abstract: Prenatal exposure to alcohol is known to affect gross motor functioning. Animal studies have shown that balance is particularly affected, and there is some evidence that similar deficits exist in alcohol-exposed children. In the current study, postural balance, or the ability to maintain equilibrium, was assessed in a group of alcohol-exposed children (ALC group; n = 11) and controls (NC group; n = 11) individually matched for age and sex. Balance was measured across six conditions designed to systematically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 43 publications
6
33
1
1
Order By: Relevance
“…Although symptoms suggestive of developmental or neurologically based immaturities were observed in children from both groups, children with FASD were three times more likely to be classified in a clinically suspect category. Results draw attention to qualitative sensory-motor differences and inefficient motor performance among children with FASD, findings described (to some extent) in earlier clinical and longitudinal prospective studies of children prenatally exposed to alcohol, but documented here using a standardized measure (Kyllerman et al, 1985;Larrouque & Kaminski, 1998;Roebuck, Simmons, Mattson, & Riley, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Although symptoms suggestive of developmental or neurologically based immaturities were observed in children from both groups, children with FASD were three times more likely to be classified in a clinically suspect category. Results draw attention to qualitative sensory-motor differences and inefficient motor performance among children with FASD, findings described (to some extent) in earlier clinical and longitudinal prospective studies of children prenatally exposed to alcohol, but documented here using a standardized measure (Kyllerman et al, 1985;Larrouque & Kaminski, 1998;Roebuck, Simmons, Mattson, & Riley, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…Given the nature of functions ascribed to the cerebellum, structural anomalies may contribute to the functional deficits commonly observed in FASD, such as in balance, bimanual coordination (Roebuck et al, 1998b;Roebuck-Spencer et al, 2004), and attention (Coles et al, 1997(Coles et al, , 2002Lee et al, 2004;Streissguth et al, 1995). In addition, vermal dysmorphology has been shown to be negatively correlated with verbal learning and memory in an alcoholexposed group (O'Hare et al, 2005).…”
Section: Cerebellummentioning
confidence: 99%
“…Infants and young children exposed to alcohol in utero have been found to exhibit delays in motor development (63). Numerous other studies of individuals with prenatal alcohol exposure have found fine motor deficits (43,64,65), poor balance (64,66), and poor coordination (67).…”
Section: Strong Evidence Has Been Presented For a Host Of Other Neuromentioning
confidence: 98%